Integrating intercultural communicative competence in to the training of translators and interpreters - Domínguez Monzón, Sahily; Rodríguez Ruiz, Mayra (My University, 2021)
Problem to deal with: The Intercultural Communicative Competence (ICC) is an essential tool in the English Language teaching and learning process, particularly in the training of translators and interpreters. In today’s globalized world, the translator/interpreter needs to acquire a certain level of ICC in order to function as a bridge between different sociocultural groups, minimizing the effects of cultural misunderstandings. Aims: To propose a set of activities for the subject Introducción a la Traducción in the third academic year of the degree course English Language with A Second Foreign Language so that students become interculturally competent translators and interpreters. Methodology: A mixed-method approach was held in this study. The sample included ten fourth-year students of the academic year 2019-2020 and five professors from the English Language Department, School of Humanities at the Universidad Central “Marta Abreu” de Las Villas. Results and Discussion: The needs analysis concerning the current situation of intercultural communicative competence in the degree course English Language with A Second Foreign Language indicated that most of the participants thought that integrating ICC into the teaching and learning process of translation would be very useful for the enrichment of students for their future professional lives. Conclusions: The activities proposed are intended to sensitize students with respect to the importance of intercultural communicative competence in their training as future professional translators and interpreters. They could be a very suitable pedagogical tool in the teaching and learning process of translation in order to foster the students’ intercultural communicative competence.

Problemática: La Competencia Comunicativa Intercultural (CCI) es una herramienta esencial en el proceso de enseñanza y aprendizaje de la lengua inglesa, especialmente en la formación de traductores e intérpretes. En el mundo globalizado actual, el traductor/intérprete necesita adquirir un determinado nivel de competencia comunicativa intercultural para poder funcionar como puente entre diferentes grupos socioculturales y minimizar los efectos que puedan ocurrir debido a malentendidos entre culturas.  Objetivo(s): Proponer un conjunto de actividades para la asignatura Introducción a la Traducción en el tercer año académico de la mencionada carrera que contribuya a que los estudiantes se formen como traductores e intérpretes interculturalmente competentes en su futura vida profesional.
Integración de la competencia comunicativa intercultural en la formación de traductores e intérpretes
Keywords: Culture; Intercultural Communicative Competence; Interculturality; Translator and Interpreter Training; Cultura; Competencia Comunicativa Intercultural; Interculturalidad; Formación de Traductores e Intérpretes; Lengua Inglesa; Enseñanza; Aprendizaje